Psychometric characteristics of the Chinese version of the Pregnancy Exercise Attitudes Scale (C-PEAS) - Xiaoting Wang; Jiaxin Ren; Hongxia Wang (BMC, 2024)
Abstract Background Reasonable instruction and promotion of appropriate exercise are crucial to improving the exercise status of pregnant women and safeguarding the health of both mother and fetus. However, there is a lack of validated Pregnancy Exercise Attitude Scales with a complete evaluation system in China. This study aims to assess the validity and reliability of the Pregnancy Exercise Attitude Scale (C-PEAS) in Chinese to give medical professionals a reference for carrying out pregnancy care services and promoting the health of the mother and fetus. Methods In this study, the scale was translated, back-translated, and cross-culturally adapted using the Brislin translation model to form the C-PEAS. 528 pregnant women were conveniently selected for the questionnaire survey to evaluate the scale's reliability. The scale's content validity was assessed by the content validity index, while its structural validity was investigated using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Cronbach's alpha coefficient, McDonald's omega coefficient, split-half reliability, and retest reliability were used to evaluate the scale's internal consistency. Results The C-PEAS contains two dimensions with 37 entries. The EFA supports a two-factor structure with a cumulative variance contribution of 62.927%. The CFA model was well fitted (χ2/df = 1.597, RMSEA = 0.048, IFI = 0.955, TLI = 0.952, and CFI = 0.955). The C- PEAS' Cronbach's alpha coefficient was 0.973, and the range of Cronbach's alpha values for the dimensions was 0.976, 0.944. McDonald's omega coefficient was 0.971, the half-point reliability of the scale was 0.856, and the retest reliability was 0.966. Conclusions The Chinese version of C-PEAS has good psychometric properties. It can be used as an effective measurement tool to evaluate the attitude of pregnant women to exercise during pregnancy.